Novel algorithm of maintaining packet order in two-stage switch - ZHANG Xiao-ning; XU Du; LI Le-min (Tongxin xuebao)
To enhance the scalability of high performance packet switches, recently a two-stage load-balanced switch was introduced by Zhang, in which each stage used a deterministic sequence of configurations. The switch was simple to be scalable and had been proved to provide 100% throughput. However, in its basic fabric, the load-balanced switch may mis-sequence the packets. A new algorithm called FFS （full frame stuff） was proposed in this paper, which maintains packet order in the two-stage load-balanced switch and has excellent switching performance （in terms of mean delay and throughput）.This algorithm is distributed and each port operates independently.